Reaction-rate function of proton-deuteron radiative capture within potential model - Dao, Nhut Anh; Do, Huy Tho; Nguyen, Le Anh (Communications in Physics, 2025)
The proton-deuteron (pD) radiative capture reaction plays a crucial role in primordial nucleosynthesis. The astrophysical S-factor is calculated using a phenomenological potential model, considering both electric dipole (E1) and magnetic dipole (M1) transitions. The resulting S-factor is found to be in good agreement with recent experimental data. In addition, an approximate polynomial expression for the reaction-rate function is provided.